Integrasi Augemented Reality dan Fun Sport Games Berbasis Aplikasi Interaktif Untuk Meningkatkan Aktivitas Fisik Anak TK di Kota Cirebon dengan Ruang Terbatas - Mia Rosalina; Zuki Kurniawan; Munaji Munaji; Nur Rahmadilla; Solihin Andhika (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2025)
This research focuses on promoting physical engagement among young learners in early childhood education environments by integrating Augmented Reality (AR) with interactive sport-based games at IGRA Pekalipan Kindergarten, Cirebon City. A developmental–implementation framework was employed, emphasizing the creation and utilization of an AR-driven application designed to support children’s movement activities within spatially constrained classrooms. The outcomes revealed a 25% improvement in both duration and intensity of physical involvement during the onemonth intervention. In addition, AR-integrated games significantly enhanced children’s participation, enthusiasm, and motor skill growth through engaging and playful learning interactions. Overall, the study demonstrates that AR innovation offers a creative and feasible strategy for fostering physical activity among early learners, particularly in environments with limited physical space.